Iść, czyli jechać. Językowy obraz świata w cyklolekcie - Wiertlewski, Stefan (Investigationes Linguisticae, 2019)
Reconstructing the specific linguistic image of the world embedded in the social varieties of language is one of the major concerns of sociolinguistics. This paper shows that in Polish cycling sociolect two common verbs iść (walk) and chodzić (walk) are used with the meaning of jechać (ride). A huge number of word complexes and phraseological units with these verb analysed by the author justify the opinion reflected in the conceptual metaphor that RIDING A BIKE IS WALKING.